Volatility Analysis on Producer Price of Red Pepper and Cayenne Pepper in West Java Province Indonesia - Candarisma Dhanes Noor Viana; Slamet Hartono; Lestari Rahayu Waluyati (Agro Ekonomi, 2017)
This study aims to determine the price volatility in producer of red pepper and cayenne pepper in West Java Province. The data used in this research was secondary data focusing on monthly price statistics of red pepper and cayenne pepper producer in West Java Province from 2008 to 2015. The method used in this research was ARCH/GARCH method with best model determination. Based on the research, it was found that the best model for the price of red pepper in producer was GARCH (1,1) with the volatility value of 0,96. It means that volatility of price of red pepper in producer level was influenced by the increase and fluctuations on producer price of red pepper one month before. The best model for the price of the cayenne pepper producer was ARCH (1) with the volatility value of 0,52. It means that price volatility of cayenne pepper in producer level was also influenced by fluctuations producer price of cayenne pepper one month before. The value of volatility price of red pepper in West Java Province is closed to one, so it can be categorized of high volatility. Meanwhile, the price on the producer of cayenne pepper in West Java Province can be categorized of low volatility.